Estudo de materiais mesoporosos funcionalizados com diferentes aminas para captura do dióxido de carbono através do processo de adsorção - Barbosa, Marcela Nascimento (2013)
Intensive use of machinery and engines burning fuel dumps into the atmosphere huge amounts of carbon dioxide (CO2), causing the intensification of the greenhouse effect. Climate changes that are occurring in the world are directly related to emissions of greenhouse gases, mainly CO2, gases, mainly due to the excessive use of fossil fuels. The search for new technologies to minimize the environmental impacts of this phenomenon has been investigated. Sequestration of CO2 is one of the alternatives that can help minimize greenhouse gas emissions. The CO2 can be captured by the post-combustion technology, by adsorption using adsorbents selective for this purpose. With this objective, were synthesized by hydrothermal method at 100 °C, the type mesoporous materials MCM - 41 and SBA-15. After the synthesis, the materials were submitted to a calcination step and subsequently functionalized with different amines (APTES, MEA, DEA and PEI) through reflux method. The samples functionalized with amines were tested for adsorption of CO2 in order to evaluate their adsorption capacities as well, were subjected to various analyzes of characterization in order to assess the efficiency of the method used for functionalization with amines. The physic-chemical techniques were used: X- ray diffraction (XRD), nitrogen adsorption and desorption (BET/BJH), scanning electron microscopy (SEM), transmission electron microscopy (TEM), CNH Analysis, Thermogravimetry (TG/DTG) and photoelectron spectroscopy X-ray (XPS). The CO2 adsorption experiments were carried out under the following conditions: 100 mg of adsorbent, at 25 °C under a flow of 100 ml/min of CO2, atmospheric pressure and the adsorption variation in time 10-210 min. The X-ray diffraction with the transmission electron micrographs for the samples synthesized and functionalized, MCM-41 and SBA-15 showed characteristic peaks of hexagonal mesoporous structure formation, showing the structure thereof was obtained. The method used was efficient reflux according to XPS and elemental analysis, which showed the presence of amines in the starting materials. The functionalized SBA -15 samples were those that had potential as best adsorbent for CO2 capture when compared with samples of MCM-41, obtaining the maximum adsorption capacity for SBA-15-P sample